Polybrominated diphenyl ethers in mussels (Mytilus galloprovincialis) collected from Central Adriatic Sea. Issue 1 (15th December 2015) - Piersanti, Arianna; Tavoloni, Tamara; Bastari, Eleonora; Lestingi, Carmela; Romanelli, Sara; Saluti, Giorgio; Moretti, Simone; Galarini, Roberta
Abstract: One-hundred and thirty-four samples of mussels ( Mytilus galloprovincialis ) collected along Central Adriatic Sea in 2013 were examined to determine the levels of fifteen congeners of polybrominated diphenyl ethers (PBDEs). The purified samples were analysed by gas-chromatography coupled to tandem mass spectrometry (GC-MS/MS) applying the isotopic dilution. Only four congeners (PBDE 47, PBDE 99, PBDE 49 and PBDE 100) were present above the established limits of quantification with mean concentrations equal to 73, 30, 19 and 18 pg g − 1, respectively. The concentrations of PBDEs (sum) ranged from 27 to 386 pg g − 1, with the highest levels around the coastal area of Ancona town. The here found levels were comparable to those measured in mussels collected along Southern Adriatic Sea. Highlights: Fifteen congeners of polybrominated diphenyl ethers have been determined in 134 mussel samples from Adriatic Sea (Italy) The found levels were low and comparable to those previosly measured in mussels collected along Adriatic coasts To obtain data comparability in PBDE analysis particular attention must be paid to quality assurance issues